The Art of Influence: Unleashing the Power of Social Media to Elevate Brand Awareness and Drive Sales for Indonesian MSMEs - Widhinata, Gusti Made Christian (LPPM Universitas Dhyana Pura, 2025)
This study examined the critical role of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia’s economy, particularly their contributions to job creation, local economic development, and community income enhancement. Despite their importance, MSMEs face challenges in effectively promoting their products in the digital era. This research explored the potential opportunities for MSME entrepreneurs to leverage social media as a marketing platform. Utilizing document study as a data collection method, the study highlighted how social media, combined with digital marketing strategies such as brand awareness and SEO, can significantly enhance MSMEs’ product visibility, consumer engagement, and sales performance. The findings aimed to provide valuable insights and new perspectives on optimizing digital marketing approaches for MSMEs to remain competitive in an increasingly digital marketplace.